CO2 versus Air Insufflation for Private Practice Routine Colonoscopy: Results of a Randomized Double Blind Trial - Mayr, M.; Miller, A.; Gauger, U.; Rösch, T. (Zeitschrift für Gastroenterologie, 2012)
Background: Pain and bloating following colonoscopy are an underestimated problem, with 30 − 60 % of patients complaining of such symptoms. The use of CO2 has been shown to significantly decrease pain after colonoscopy in academic hospital-based studies. The aim of the present study was to evaluate whether such an effect can also be seen during private practice routine colonoscopy.Patients and Methods: In a prospective double-blind randomized trial, one experienced colonoscopist (> 12 000 examinations) used either air or CO2 insufflation for diagnostic or screening colonoscopy in consecutive patients presenting for diagnostic and screening colonoscopy in private practice. Outcome parameters were occurrence and duration of pain and bloating after colonoscopy based on a patient questionnaire. Results: Of 180 randomized patients, 156 replies were analyzed (43.3 % male, mean age 61.7 ± 9.7 years). There were no significant differences between the two groups with respect to age and sex distribution, indication, sedation, examination times and polypectomy rates. Both pain and abdominal bloating were significantly lower in the CO2 group. Abdominal pain and bloating in the CO2 vs. air group were absent in 84.4 vs. 64.6 % (p = 0.005) and 66.2 vs. 32.9 % (p < 0.001). Moderate/strong symptoms were also significantly lower with CO2.Conclusions: The use of CO2 appears to be as effective in daily routine in private practice colonoscopy as reported in previous hospital-based studies.
Keywords: colorectal adenoma; colorectal carcinoma; irritable colon